Evaluation of a new job training program: Code Louisville. - Bollinger, Christopher R.; Troske, Kenneth R. (Journal of Policy Analysis & Management)
This article evaluates the labor market impacts of Code Louisville, a sectoral job training program in Louisville, Kentucky, that provides online training in computer software development and is administered by the local Workforce Development Board, KentuckianaWorks. Using matched administrative data from the Kentucky Longitudinal Data System, the study finds that male participants experience significant employment gains (about 5 percentage points within one year) and modest earnings increases (5–10% by three years), while female participants see earlier and larger earnings gains (up to 15% by three years) but smaller employment improvements. Benefits are concentrated among participants who complete at least one training module and those with a bachelor’s degree or higher, with limited effects for less-educated individuals. Compared to other federally funded programs, Code Louisville’s impacts are similar or slightly better but smaller than nongovernmental sectoral training programs, though its substantially lower cost suggests it may be an efficient model for delivering job training.